PENGEMBANGAN KONSEP SUBANG SMART CITY DENGAN PENDEKATAN ANALISIS SOAR DAN PERSFEKTIF CO-CREATION - Kuncorosidi Kuncorosidi; Ghanssani Nur Khasanah Putri (STIESA-PRESS, 2024)
Their technology brings ease of information to the public. Through an application, a variety of information about the city can be accessed quickly by society and the government through the Program called Smart City. Smart City is already implemented in many cities in the world and has proven able to resolve problems as quickly as well. The information can also be utilized Government to create comfort, safety, and order and, a better life. Smart people are the basis of the realization of Smart Cities. This relates to the formation of smart cities, which must have intelligent human resources and be supported by policies and infrastructure of mobility, governance, economy, and environment that are also smart to produce the quality of life as intelligent as desired. A smart city is a smart city concept designed to help various community activities and provide easy access to information to the public. This concept emphasizes three concepts, first, a concept applied by the local government system in managing urban society, the second, a concept that required the management of the region against all resources effectively and efficiently and the thet is smart city is expected to be able to carry out the information provider function appropriately to the community and be able to anticipate unexpected events. The study formulated the Subang Regency strategies towards a smart city in each smart city's dimensions. These strategies include accelerating public services, quick decision-making on Subang's problems, and supporting the Subang area monitoring system; hence regional heads and related agencies can obtain the latest information and act responsively.